Anti-Müllerian Hormone Expression in the Ovarian Follicles and Factors Related to Serum Anti-Müllerian Hormone Concentrations in the Domestic Queens - Gözer, A; Dogruer, G; Gokcek, I; Kutlu, T; Bahan, O; Pır Yagcı, I (Journal of the Hellenic Veterinary Medical Society, 2024)
Antimüllerian Hormone (AMH) is a glycoprotein with 140 kDa molecular weight secreted by the granulosa cells, belonging to the transforming growth factor-β family. Antimüllerian Hormone plays a crucial role in folliculogenesis. The present study aimed to reveal (1) the relationship between age, body weight, sexual cycle, and ovariohysterectomy with the serum antimüllerian hormone concentrations and (2) ovarian expressions of the AMH in the ovarian follicles. Serum AMH concentrations were determined by the commercial ELISA (Beckman Coulter Gen II) immunoassay. The immunohistochemical method determined ovarian expressions of the AMH in the granulosa cells. Twenty cats admitted to Hatay Mustafa Kemal University Veterinary Faculty of Obstetrics and Gynaecology Clinics were included in the current study. Cats were allocated to three groups according to the period of the sexual cycle, age, and body weight. The sexual cycle was determined by the estradiol 17-ß and progesterone measurement. Blood samples were collected into tubes without anticoagulant to determine serum AMH concentration at preoperative (Day 0), postoperative 3rd and 10th days. There was a decrease in the third postoperative days of AMH levels compared to the preoperative level (0th) (p<0.001). No statistical differences were found between postpartum 3rd and 10th days (p>0.05). It was observed that the period of the sexual cycle, age, and body weight did not affect the AMH level (p>0.05). In immunohistochemical analyses, it was observed that a mild AMH expression was first observed in granulosa cells of the primary follicles. Moderate AMH expressions were observed in the granulosa cells of the secondary follicles. While strong AMH expression was observed in the cumulus cells of the antral follicles, mild AMH expressions were in the mural granulosa cells of the antral follicles. In conclusion, ovariohysterectomy was the only determinant of serum AMH concentration, and AMH expression in the ovarian follicles shows the stage-dependent characteristic in domestic cats.